Ubiquity Photography's Multitudes - Lewis, Jacob W.; Parry, Kyle (Leuven University Press, 2021)
From its invention to the internet age, photography has been considered universal, pervasive, and omnipresent. This anthology of essays posits how the question of when photography came to be everywhere shapes our understanding of all manner of photographic media. Whether looking at a portrait image on the polished silver surface of the daguerreotype, or a viral image on the reflective glass of the smartphone, the experience of looking at photographs and thinking with photography is inseparable from the idea of ubiquity-that is, the apparent ability to be everywhere at once. While photography's distribution across cultures today is undeniable, the insidious logics and pervasive myths that have governed its spread demand our critical attention, now more than ever.